Protection of Refugees under International Law: The Case of Iraqi Kurdistan Region Refugees - Sanh Shareef Qader; Nishtiman Othman Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Refugeehood is a state that does not only occur due to political matters. It is a state that can come about as a result of natural disasters – famine, earthquakes, drought and flood. International law principles safeguard the protection of refugees as stated in the 1951 Convention and 1967 Protocol relating to the status of refugees, as well as in other international and regional instruments. The rights of refugees mainly includes non-refoulement, no penalties on the illegal entry of refugees, right to life, right of physical security, life necessities, right of family unity, education, access to justice, employment, and other fundamental freedoms. This paper aims to examine the living situation of refugees in the Iraqi Kurdistan region and whether their rights are provided by the Kurdistan Regional Government (KRG). This paper will also look at whether the financial aid of KRG corresponds with international law standards for protecting the refugees rights. This paper focused on secondary sources to analyze various opinions and come to conclusions. The study found that refugees’ rights have international legal protection and that states and governments have a responsibility to respect those rights. The findings also showed that the aid provided by the KRG corresponds to international law principles.